Return-to-work outcomes and usefulness of actual fit notes received by employers - Coole, Carol; Potgieter, Iskra; Nouri, Fiona; Worthington, Esme; Drummond, Avril (Oxford University Press, 2015)
Background: GPs can use the fit note to advise that a patient ‘may be fit’ or is ‘not fit’ for work. Previous employer-based research on the fit note is largely qualitative and based on general perceptions and past experience. Knowledge of the return-to-work outcomes and usefulness of actual fit notes is needed to strengthen the evidence-base and inform practice. Objective: To investigate the return-to-work outcomes of fit notes issued to employed patients, and their employers’ opinions as to the usefulness of each note. Methods: Participating organizations collecting fit notes were asked to rate the outcome and usefulness of each fit note via postal questionnaires. Quantitative data were analysed descriptively; qualitative data were analysed using thematic content analysis. Results: Five hundred and sixteen questionnaires were posted, with a 97% return rate (n = 498). More than 80% of employees (n = 44) returned to work after the expiry date of a ‘may be fit’ note compared with 43% (n = 167) of those issued with a ‘not fit’ note. Fit notes were considered more useful if they provided information on the condition and its effect on the employee’s ability to work, if they stated whether or not the employee needed reassessment and if clear advice regarding return-to-work had been provided. Conclusions: ‘May be fit’ notes are useful in helping employees return to work. However, this option is infrequently used, and the completion and content of many fit notes does not meet employers’ needs. These factors need to be urgently addressed if the fit note is to reach its full potential.